Implementasi Konsep Balanced Scorecard (BSC) Berbasis Syari’ah Dalam Pengukuran Kinerja - Riswanto, Anang Yudi; indupurnahayu, Indupurnahayu; Amin, Akhmad Bakhtiar (Jurnal Manajemen, 2018)
The purpose of this research is to measure the performance of PT Mutiara Global Industry by using Sharia-based Balance Scorecard method. This research is quantitative research with descriptive approach. Performance measurement of PT Mutiara Global Industry from a financial perspective, customer perspective, intenal business process perspective and learning and growth perspective. The Shariah aspect in the financial perspective is the source of capital and the allocation of profit for zakat, infaq and alms. In the customer's perspective is how to keep the promise to the customer by always being sidik, tabligh, amanah and fathonah. In the internal process business perspective is emphasized on itqan, working with perfect and complete quality and ihsan, always feeling watched by God. In the perspective of learning and growth is to control the charity of worship and study syar'i. Sampel from this research are employees and customers of PT Mutiara Global Industry This research concludes that the performance of PT Mutiara Global Industry is good category (score: 3,46875). The Accumulation results from financial perspective score 0.964, customer perspective score 0.9375, internal process perspective score: 1 and learning and growth perspective 0.6875 To improve the performance of PT Mutiara Global Industry is recommended for (1) improvement of ISO system implementation, (2) improvement of coaching and implementation of employee worship, (3) improvement of communication and service to customer (4). Improvement of process and product quality, (5). Improvement of inventory management that will be impact on the on time of production schedule.